RESEARCH OF THE POSSIBILITY OF THE USING OF WASTES ENRICHMENT OF GOLD-CONTAINING ORES IN THE PROCESS OF RECEIVING SILICOPHOSPHATE FERTILIZERS BY MECHANOCHEMICAL ACTIVATION - V.I. Kapralova,; Sh.N. Kubekova,; G.T. Ibraimova,; M.Zh. Kussainova,; M.Zh. Kussainova,; A.S. Raimbekova,; K.Sharipov, (Academic Scientific Journal of Chemistry, 2019)
The material and phase composition of the wastes enrichment of the gold-bearing ore of the Pustynoye deposit were studied and it was shown that quartz and silicon compounds are their main productive phase, their content in recalculate on silicon dioxide is 75.13 mass.%. With the using of the mechanochemical activation (MCA)method by dry process a silicon-phosphate material was obtained with the component ratio of Karatau phosphorite: enrichment waste = 1: 1. It has been established that mechanically activated phosphorite mixture with wastes of ore enrichment of "Pustynoye" deposit contains 1.4% of water-soluble form of phosphorus pentoxide and 51.7% of citrate-soluble P2O5. In this case, the product is completely soluble in citric acid. While the original phosphorus does not contain a water-soluble form of phosphorus pentoxide, and the content of citrate- and citronsoluble forms of P2O5 is (rel. %) 8.6 and 58.5, accordingly. Mechanochemical activation of mixtures of natural phosphates with waste of enrichment of gold-bearing ore promotes the appearance in the aqueous extract of assimilable compounds of silicon in the form of monosilicic acid in the amount of 62.5 mg / l, whereas in the original phosphorus these compounds are absent. Also it has been shown that in the silicophosphative-containing product after MCA the fluorine content significantly reduces, from 3.11 to 1.21 wt%. The carried out researches have shown the possibility of using of wastes enrichment of gold-bearing ore of "Pustynoye" deposit in the processes of obtaining silicophosphate fertilizers by the method of mechanochemical activation.